R&D and education resources in innovation processes: evidence from Slovenia and the Visegrad Group. (2016) - Ruzzier, Mitja; Antolič, Tanja Kosi; Omerzel, Doris Gomezelj
This article provides a cross-country analysis of the efficiency and effectiveness of innovation processes in the European Union countries, with a focus on Slovenia and the four countries of the Visegrad Group (the Czech Republic, Hungary, Slovakia and Poland). By examining relationships between different composite innovation indicators, our study reveals patterns in the input-output-outcome relationships at different stages of the innovation process and highlights country-specific bottlenecks and possible efficiency gains in the use of R&D and education resources. Benchmarking the effectiveness and efficiency of innovation systems and processes across selected countries is valuable for different target groups, to whom we offer insights into the R&D environment, barriers to technology transfer and possible improvements in innovation policies.